Die behoefte aan dinamiese tersiêre Geskiedeniskurrikula tot voordeel van mededissiplines en gunstiger beroepsmoontlikhede - Eeden, E. S. van (Koers, 1993)
The study of History in South Africa demands high standards in the rapidlychanging late twentieth century. Standards require reform and change in research themes, in methodology and in the instruction of the discipline. During the seventies and eighties the practice of History has already been characterized by much reform. For example, some aspects of curricula on tertiary level changed from a purely chronological approach and began to lean towards the inclusion of innovative and contemporary relevant themes of periods perceived as significant. Presently, however, commentators from other disciplines still think of History as a subject dealing only with endless facts embedded in past politics. The mam reason for this distorted image is probably that the trend of reconstructing History curricula is not being sufficiently explored or marketed at the tertiary level. This emphasises the task of the historian to adapt curricula dynamically in order to enhance other disciplines to their benefit. Adaptation will have the added advantage of improving employment for graduates with a training in History. In this article the dynamic change which tertiary History curricula should adopt in order to improve disciplinary curricular interaction and favourable employment opportunities is discussed.